Semantic coordinates of research on extracurricular education program quality assessment - Loginova, Larisa (Opción, 2019)
In the climate of the modern market economy, education is the major criterion for producing a competitive specialist. The problem is that their quality assessment is rather challenging, as the assessment criteria are flux. The purpose of this article is to identify and consider the main criteria for American Electric Power (AEP) quality assessment. This goal was achieved by means of complementary research methods: generalization, comparative analysis, and synthesis. Research result is that we considered seven leading criteria that should guide AEP quality assessment. This will allow picking education programs of higher quality. This will affect the intellectual development of the younger generation.